2014
DOI: 10.1002/ebch.1975
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane in context: Pharmacological interventions for hypertension in children

Abstract: Overall, there are sparse data informing the use of antihypertensive agents in children, with outcomes reported limited to blood pressure and not end-organ damage. Most data are available for candesartan, for which there is low-quality evidence of a modest lowering effect on blood pressure. We did not find evidence of a consistent dose–response relationship for escalating doses of angiotensin receptor blockers, calcium channel blockers or angiotensin-converting enzyme inhibitors. All agents appear safe, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…There are precarious data on the long-term sequelae of persistent hypertension in children, but it is known that there is evidence of target organs and risk hypertension in adulthood. In most cases, nonpharmacological measures are recommended as first-rate therapy, but a significant proportion of children will need pharmacological treatment to control SAH, especially those with evidence of target organs, but also for those who fail Lifestyle modifications, which have chronic kidney disease and/or diabetes mellitus with hypertension, symptomatic hypertension and stage 2 hypertension at presentation or during followup (Chaturvedi;et. Al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…There are precarious data on the long-term sequelae of persistent hypertension in children, but it is known that there is evidence of target organs and risk hypertension in adulthood. In most cases, nonpharmacological measures are recommended as first-rate therapy, but a significant proportion of children will need pharmacological treatment to control SAH, especially those with evidence of target organs, but also for those who fail Lifestyle modifications, which have chronic kidney disease and/or diabetes mellitus with hypertension, symptomatic hypertension and stage 2 hypertension at presentation or during followup (Chaturvedi;et. Al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The most common comorbidities in the study population were dyslipidemia, diabetes mellitus, cardiovascular diseases, and obesity, which is supported by the findings of the study by Alkaabi et al (2019) [ 15 ]. As per the literature, insulin resistance and obesity play a central role in causing HTN and dyslipidemia [ 16 ]. Very few Indian studies have been published on the correlation between screen time exposure and HTN.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review found 21 randomized controlled trials, usually of short duration and without placebo control groups. Most studies showed BP lowering effects of antihypertensive drugs without severe adverse effects (Grade B) ( 28 ). However, no pediatric randomized controlled trials have investigated the efficacy of any antihypertensive drug on the prevention or regression of HMOD.…”
Section: Treatmentmentioning
confidence: 99%